ON THE INFLUENCE OF THE POROSITY OF FINE-GRAINED CONCRETES AND DRY BUILDING MIXTURES ON CONTACT ZONE FROST RESISTANCE - G. N. Nesvetaev; A. V. Dolgova; G. N. Khadzhishalapov; M. M. Batdalov (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives This study was aimed at identifying the dependency of the frost resistance of the contact zone of fine-grained concretes (FGCs) obtained from dry building mixtures (DBMs) based on various Portland cements (PCs) with the content of various redispersable polymer powders (RPPs) from 0 to 3%.Method The research was based on 75 freeze-defrost cycles.Results Although the average dependency of adhesion with the base on additional porosity after 75 freeze-defrost cycles does not depend on the nature of NMV, adhesion is influenced by the cement type, the type and dosage of RPPs, as well as the nature of additional porosity. Since the content of organised volume of NMV in the form of VV has no effect on changes in adhesion with the concrete base following 75 freeze-defrost cycles, it is impractical to add more than 7% of NMV in the form of MS to the concrete mixture. The feasibility of using sulphate-resistant cement requires more research. The practical RPP dosage should be 1-2%. Some contradictions in conclusions on the volume of the introduced MS (by the strength criterion – at least 6%, by the criterion of frost resistance of the contact zone – no more than 7%) allows us to recommend the dosage of MS in RPP within 6-7% by volume for obtaining additional data on the MS effect on frost resistance.Conclusion The dependency of compressive strength on additional porosity for FGCs without NMV and with NMV in the VV form after hardening during 28 days under normal conditions almost coincides with the known dependency of strength on porosity for cement stone; the maximum divergence of the values ???????? ????0 in the investigated range does not exceed 5%. The dependency of compressive strength on additional porosity for FGCs without NMV and with NMV in the MS form is similar to the known dependency of strength from porosity for cement stone; however, with increasing porosity, there is a slight decrease in the effect of porosity on strength. The dependency of compressive strength after 75 freeze-defrost cycles on additional porosity for FGC without NMV practically coincides with the previously obtained dependency of strength on porosity for cement stone; the maximum divergence of the values ???????? ????0 in the investigated range does not exceed 9%. For FGCs with NMV in the MC form, increasing porosity causes a slight decrease in the porosity effect on strength, and for FGCs with NMV in the VV form, the dependency has a quantitative and qualitative difference. The value of NMV in the VV form recommended for improving the frost resistance of FGCs by the strength criterion is at least 3%, MS – at least 6%. According to the criterion of the frost resistance of the contact zone and the strength of MS, the recommended dosage is 6-7%. It was not possible to disclose the direct impact of the VV volume on the frost resistance of the contact zone.